Education policy between persistence and change: grand transformations processes and cultural spheres in the case of Cambodia - Bao, Fangyue; Martens, Kerstin; Windzio, Michael (Frontiers in Education, 2025)
In this study, we aim to understand how international influences, moderated by cultural spheres, impact the inclusiveness of education and support generosity for individuals’ education in the long durée. The two grand and globally significant political transformation processes we focus on are (de)colonization and socialism. We also analyze how current multilateralism exerted through international organizations (IOs) in the post-WW2 order affects national education policies. For this purpose, we exercise a case study on Cambodia, which lived through colonization, socialist ruling, and other internal conflicts. We are interested in how these processes have left their traces in Cambodia’s education system. This work is a case study analyzing qualitative data from semi-structured interviews and official documents from governments and other sources. The article argues that today’s education system in Cambodia is based on the education model established by the French during its colonial period and later developed to accommodate its cultural and religious traditions. The socialist regime led to heavy losses in Cambodia and damaged most education facilities. In over 30 years, Cambodia’s education has recovered with support from the international community, along with the international standards on education inclusion and generosity.